Xanthogranulomatous prostatitis mimicking prostate carcinoma: a case report and comprehensive literature review - Mingfeng Ji; Yihao Chen; Haoxuan Feng; Jiasong Wang; Haozhen Li; Heyao Tong; Zhuwei Song; Qimin Wang; Zhihong Dai; Bo Fan (Frontiers in Medicine, 2026)
Introduction Granulomatous prostatitis (GP) is a relatively uncommon disorder, accounting for approximately 0. 8% to 1.0% of all benign inflammatory prostatic conditions. Xanthogranulomatous prostatitis (XGP) is an exceptionally rare subtype of GP, with only a limited number of cases documented in the medical literature. Clinically and radiologically, this entity often mimics prostatic carcinoma, necessitating histopathological examination for an accurate diagnosis. Case presentation A 69-year-old man presented with a multi-year history of urinary frequency, nocturia, dysuria, and dull flank pain. Clinical evaluation and laboratory studies revealed an elevated prostate-specific antigen (PSA) level. Ultrasonography demonstrated prostatic enlargement with heterogeneous echogenicity and a 1.7-cm intravesical protrusion. Prostate magnetic resonance imaging (MRI) indicated a prostatic volume of 46.33 cm 3 . A lesion measuring up to 2.4 cm in maximum diameter was localized to the right basal transitional zone and right basal fibromuscular stroma. The lesion exhibited low signal intensity on T2-weighted imaging, hyperintensity on diffusion-weighted imaging (DWI), and restricted diffusion with a correspondingly low signal on the apparent diffusion coefficient (ADC) map. Bladder involvement was also noted, yielding a Prostate Imaging Reporting and Data System (PI-RADS) score of 4. The patient subsequently underwent transurethral resection of the prostate (TURP) as a therapeutic intervention. Histopathological examination of the resected tissue confirmed the diagnosis of XGP. Conclusion XGP is an extremely rare prostatic pathology, and histopathological examination remains the gold standard for definitive diagnosis. Conservative management and TURP constitute the recommended therapeutic approaches for this condition.